Protection and Intellectual Rights in Over-The-Top (OTT) Services: A Juridical Analysis of HBO Go Inconsistencies Indonesia - Ilhamda Fattah Kaloko; Rian Rusmana Putra; Eka Yeremy Augie Putra Jacharia; Ario Ardanis Nainggolan (Mahadi: Indonesia Journal of Law, 2026)
The rapid development of information and communication technology has significantly transformed public consumption patterns, particularly in accessing digital entertainment through internet-based services known as Over The Top (OTT) platforms. Services such as HBO Go operate through subscription-based models that provide flexible, on-demand access to audiovisual content; however, in practice, legal issues frequently arise, including inconsistencies between promised and delivered services and widespread violations of intellectual property rights through digital piracy. This article aims to (1) analyze the legal implications of service inconsistencies experienced by HBO Go users from the perspective of Indonesian consumer protection law, (2) examine the relationship between such inconsistencies and copyright protection in digital content distribution, and (3) evaluate the adequacy of Indonesia’s current regulatory framework in comprehensively governing OTT services. The study employs a normative legal research method using statutory, conceptual, and case approaches by analyzing relevant legislation, particularly Law Number 8 of 1999 concerning Consumer Protection and Law Number 28 of 2014 concerning Copyright, alongside factual cases involving consumer complaints related to access disruptions, unilateral subscription changes, lack of transparency, and digital content piracy, including the illegal distribution of the television series Game of Thrones. The findings indicate that service inconsistencies such as access disruptions, unilateral modifications of subscription packages, and inadequate information disclosure may constitute violations of consumer rights under Indonesian law, while the high prevalence of piracy reflects weaknesses in digital copyright enforcement, resulting in economic and moral losses for content creators and undermining the credibility of legitimate OTT platforms. The study concludes that Indonesia faces a regulatory gap in comprehensively governing OTT services, thereby necessitating the establishment of a specific and adaptive legal framework to ensure effective consumer protection, strengthen intellectual property enforcement, and promote a fair, transparent, and sustainable digital ecosystem.